Electrical behavior of proton-conducting chitosan-phosphoric acid-based electrolytes - Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2007)
Dielectric and AC conductivity studies have been carried out for chitosan-based proton-conducting electrolytes. Chitosan-phosphoric acid (CP) and chitosan composite (CPS) electrolytes were prepared using the solution cast method. In both systems, the frequency dependence of epsilon(r), M-i and tan delta is non-Debye type. The AC conductivity in both electrolytes follows the Jonscher power law. Conduction mechanism studies show that the CP sample follows the quantum mechanical tunneling (QMT) model and the CPS electrolyte follows the overlapping large polaron-tunneling (OLPT) model. (c) 2006 Elsevier BN. All rights reserved.